Safety monitoring analysis in a construction site using eye-tracking method - Akcay, Cemil (Revista de la Construcción. Journal of Construction, 2022)
Construction work is one of the most dangerous business lines. As a result of occupational accidents in construction works, there are consequences that will affect human life such as injury and death, as well as serious financial losses. Especially in developing countries, despite the increase in precautions regarding occupational safety, occupational accidents continue to occur. Human behavior is an important factor in construction work accidents. In the sector where generally low-educated level workers work, analyzing the precautions and occupational safety training results are important to reduce construction work accidents. Eye-tracking technique, a technology that is spreading around the world, finds its place in different sectors. Especially with the use of mobile eye trackers instead of fixed eye trackers, this eye-tracking technology has also become usable in site implementations in the construction industry. In the construction sector, some studies are done especially on occupational safety issues using eye-tracking techniques in recent years. In this study, a site study was done with construction workers using a mobile eye-tracking approach by creating a track with different hazard sources in construction where a fatal occupational accident occurred. In this context, the attention levels of construction workers against different sources of danger and the risk of accidents created by these sources were measured with the mobile eye-tracking technique. The results obtained from the study were shared with the occupational safety experts on the site and the results are interpreted. All workers participating in the experimental study were workers that previously got occupational safety training. Therefore, according to the outcomes of this experiment, the effectiveness of the occupational safety training they received is measured and some suggestions are made.